PENERAPAN METODE PEMBELAJARAN KOOPERATIF TIPE POINT COUNTER POINT DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS VIII A PADA MATA PELAJARAN SEJARAH KEBUDAYAAN ISLAM DI MTS NEGERI SENTAJO FILIAL SINGINGI KECAMATAN SINGINGI KABUPATEN KUANTAN SINGINGI - Feni Nazela; Zulhaini Zulhaini; Helbi Akbar (AL-HIKMAH (Jurnal Pendidikan dan Pendidikan Agama Islam), 2020)
The purpose of this study was to determine how the application of the Point Counter Point method in SKI subjects in class VIII A Sentajo Filial Singingi State MTs and to find out whether the point counter point method could improve students' learning motivation in class VIII A on SKI subjects in MTs Negeri Sentajo Filial Singingi The research methodology consisted of the location of this study in MTs Sentajo Filial Singingi District Singingi District Kuantan Singingi District. The subjects of this study were one teacher of Islamic Cultural History and all students of class VIII A at MTs Sentajo Filial Singingi District Singingi District Kuantan Singingi totaling 19 people consisting of 9 men and 10 women. The object of this research is the application of the Point Counter Point Method to increase student motivation in the subject of the History of Islamic Culture class VIII A at MTs Sentajo Filial Singingi Singingi District. The population and sample were 1 SKI teacher and 19 students. Data collection techniques are observation, interviews and documentation. The data analysis technique is CAR that consists of pre cycle, cycle I, cycle II and cycle III. The conclusion from the results of the application of the Point Counter Point cooperative learning method is seen from the Pre-Cycle observation results (before the application of the PCP method) it is seen that only 21.04% of students have motivation in participating in SKI learning, in Cycle I it turns out 32.10% of students have been motivated in the SKI learning process, in Cycle II it turned out to have reached 46.15% and in Cycle III it turned out to be 50.52%. This proves that the application of the Point Counter Point method can increase student motivation.